2001
DOI: 10.1034/j.1399-302x.2001.016005279.x
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of the coadherence of Candida albicans with oral bacteria by dietary sugars

Abstract: Interactions between bacterial oral flora and Candida albicans are important in denture plaque formation. This study therefore first aimed to quantify the coadherence of C. albicans and bacteria by the use of a bioluminescent adenosine triphosphate (ATP) assay based on the firefly luciferase-luciferin system. The second aim was to examine the effect of i) dietary sugars (used for preculture) and ii) enzymatic digestion of fungi on the coadherence. When yeast was preincubated in yeast nitrogen base medium (YNB)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 41 publications
0
30
0
2
Order By: Relevance
“…Given that C. albicans has efficient adherence mechanisms, its colonization of the oral environment might represent a predisposing factor favoring its interaction with S. mutans, as has been suggested by several authors (1,23,26,35). Most studies on the in vitro interaction between two microorganisms use either reference strains or isolates from different hosts (6,(24)(25)(26). The use of isolates from hosts colonized by both microorganisms can be a starting point to future findings in specific populations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Given that C. albicans has efficient adherence mechanisms, its colonization of the oral environment might represent a predisposing factor favoring its interaction with S. mutans, as has been suggested by several authors (1,23,26,35). Most studies on the in vitro interaction between two microorganisms use either reference strains or isolates from different hosts (6,(24)(25)(26). The use of isolates from hosts colonized by both microorganisms can be a starting point to future findings in specific populations.…”
Section: Discussionmentioning
confidence: 99%
“…According to Soll (33), C. albicans is capable of differentiation, showing yeast-like and filamentous developmental forms in association with both disease and commensalism, although the yeast-like form is more prevalent in the case of comensalism. Nikawa et al (24) analyzed the coadherence of C. albicans with oral bacteria and also found a predominance of blastospores during the co-adhesion with S. mutans in a culture medium supplemented with sucrose. These authors considered the coaggregation as a key factor in the ecology of oral biofilms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it has been reported that C. albicans may prolong the viability of ␤-hemolytic streptococci (Burnet and Sherp, 1968). Furthermore, C. albicans co-aggregates with a variety of streptococci such as S. gordonii, S. mutans, and S. sanguis (Holmes et al, 1995;Nikawa et al, 2001). This may promote their colonization and thus explain the concomitant occurrence of these microbial species.…”
Section: Accompanying Bacteria In Yeast Infectionsmentioning
confidence: 99%